Preparation of Community-Based Merdeka Curriculum Teaching Modules for The Association of Raudlatul Athfal Teachers (IGRA) in Surakarta City - Khasan Ubaidillah; Tri Utami; Mila Faila Shofa; Hanik Fitriyatun; Nurul Afiyah; Salamah Az Zahra; Hilma Aziza (Transformatif: Jurnal Pengabdian Masyarakat, 2026)
The lack of training facilities regarding the implementation of the Merdeka Curriculum for Raudlatul Athfal (RA) teachers constitutes a significant obstacle in curriculum adoption. This community service program aims to develop community-based Merdeka Curriculum teaching modules for the Association of RA Teachers (IGRA) in Surakarta City. Employing a qualitative descriptive method with a Community Based Research (CBR) approach, the program actively involved 67 RA teachers from 33 institutions under IGRA Surakarta. Data were collected through interviews, Focus Group Discussions (FGD), observation, and pre-test/post-test assessments. The results demonstrate that the CBR approach effectively enhanced teacher competence, with overall understanding improving by 51%, particularly in teaching module components (from 20% to 90%). The program produced 67 teaching modules, 33 P5PPRA modules, and 33 sets of assessment instruments, with 80% of modules achieving "Good" or "Excellent" quality ratings. The success of the program underscores the importance of strategies, training, continuous mentoring, human resource strengthening, and collaboration with relevant stakeholders. This participatory approach successfully provided in-depth understanding and practical skills to RA teachers, enabling them to develop teaching modules relevant to early childhood developmental needs.